Oralidade em práticas na educação infantil - Oliveira, Arineyde Maria D’Almeida Alves de (2019)
Early Childhood Education is the first stage of Basic Education. In it, the child has the opportunity to broaden their vocabulary through the various situations of interaction with the other and develop their language skills. The appropriation of oral language happens through the genres which are configured as the basis of verbal communication and are conditioned by several communicative situations. Thus, it is important to use oral genres as an object of teaching in order to promote a reflection on the social use and function of language. In the Referencial Curricular Nacional para a Educação Infantil (1998) oral language was already considered one of the priority domains of Portuguese language teaching, as evidenced in the new document on the curriculum of Early Childhood Education included in the Base Nacional Comum Curricular (2017), in which the importance of the valorization of work with the oral language is also emphasized. Despite this, the discussions are still insufficient to have orality as an object of teaching in the classroom. Based on these arguments, it was decided to carry out this research, which had as objective to investigate how orality is worked in the classroom of children's education, based on the Referencial Curricular Nacional para a Educação Infantil - RCNEI (1998) and its Base Nacional Comum Curricular - BNCC (2017). Specifically, it sought to verify if the pedagogical practices enabled the development of the oral language of the children, as well as to know the teaching conception about the teaching of orality in Early Childhood Education. Theoretically, the present research is based on the conception of orality as a modality of the language that is realized in social contexts of interaction and has as theoretical support the studies realized by Vygotsky (1991, 2001a, 2001b), Bakhtin (2000; Dolz, Noverraz and Schneuwly (2013), Marcuschi (2001; 2002; 2007; 2008), Faria and Cavalcante (2009), among others. Methodologically, we conducted a field study in a classroom of Early Childhood Education of a public school in the city of João Pessoa – PB. The research participant was a teacher of the Pre II class, composed of five-year-old students. It was used as strategy the systematic observation recorded through a research journal, photos and footage of the moments of the activities proposed by the teacher. The corpus of the research also had a transcribed interview that sought to know the conceptions of the teacher about the teaching of orality. The analyzes made possible to organize some considerations about the practice of oral teaching in early childhood education. In general, the results pointed to the need for a theoretical deepening regarding the systematic work with oral genres in the classroom. However, it is evident that the work with oral language, despite being contemplated in the classroom, requires the teacher to plan the pedagogical action that allows structuring systematic activities about oral genres which enable children to act linguistically proficiently in front of different communication situations.